PERAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP PERILAKU INOVATIF MAHASISWA DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Asih, Wenny Murdina; Kamil, Insannul; Indrapriyatna, Ahmad Syafruddin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
Students must be able to adapt the challenges of the Industrial Revolution 4.0, so there is a need for efforts to align expertise. This research was conducted to see the role of entrepreneurship education in influencing the ability of students' technopreneurship towards innovative behavior of students with the skills of the Industrial Revolution era 4.0 as a mediating variable. The population in this study were Andalas University Padang students. Determination of the size of the sample based on percentages according to the Yount Table. Based on these considerations, the sample in this study amounted to 252 Andalas University students from 15 Faculties at Andalas University, Padang. 162 respondents have received Entrepreneurship Education (Group I) and 90 respondents have not received Entrepreneurship Education (Group II). Data collection was carried out using a closed questionnaire with a Rating scale measurement. Data obtained from the questionnaire was processed using the Structural Equation Model Partial Least Square (SEM PLS) method using the help of Smart PLS software. From this study it can be concluded that there is a role in Entrepreneurship Education in influencing the ability of student technopreneurship towards innovative behavior of students with the skills of the Industrial Revolution era 4.0 as a mediating variable.